A State Trading Enterprise for Grains in Russia? Issues and Options - World Bank (Washington, DC, 2014)
The impact of state trading enterprises (STEs) on domestic and international grain markets has been studied extensively over the years, generating a considerable body of theoretical and empirical evidence. The aim of this note is to draw on this body of evidence to analyze possible options for Russia's future state involvement in grain trade. The note covers the following three parts: i) outline of the potential economic impacts of STEs in grain trade from an economic perspective; ii) review of some of the global experience with STEs that are involved in grain exports; and iii) evaluation of options for state involvement in grain trade in Russia. The coverage in this note is limited to grains and to the impacts of STEs in countries that are net exporters of grain. Of the major grains, the note focuses on wheat which is by far the most important Russian export grain. Importing STEs are much more numerous than exporting STEs worldwide. However, unlike Ukraine, which has jumped between net export and net import situations for wheat as recently as 2003/04, it appears that Russia has become a consistent exporter since the beginning of this decade, even in years with relatively poor crop conditions. The note is further limited to the analysis of STEs and not grain market regulation in general (i.e. market and price support, income support for grain producers). However, as is discussed, such regulation can be used to help an STE pursue certain objectives by enhancing its market power, and STEs are generally implemented as part of an overall grain market regulation strategy.